F.A.Steytler : 'n waardering (Historia, 2021)
Perhaps  one  of  the  most  admirable   characteristics   of  Mr.   Steytler  washis  zest  for   history.     He  approached   it  with   a  gusto  that  is  unfortunatelyall   too  rare   and  one  recalls   his  excited  summons  of  "Kom   kyk   hierso!"when  he  unearthed   a  humorous   item   or   document  of   significance   amongthe   archival    records   or   his   triumphant     return    from   the   battlefield ofUlundi    with   old   cartridge    cases  and   fragments   of   shells.     In   the   veldwhich  he  loved,  he  had  a  keen  eye  and  an  uncanny  instinct   for  turning   upi~resting relics.     He  capped  a  life   of  rich   experience  with   illuminatinganecdotes  and  gave  his   colleagues  and  friends   revealing   glimpses   of  thepioneers   of  humble   farm   schools  in  the  Free  State  and  of  those  in   highplaces   whom   he  had   known   intimately,    especially   General  Hertzog   andMr.   N.  C.  Havenga
Keywords: Steytler, F.A.; Historian